Association between triglyceride glucose index and atherosclerotic plaques and Burden: findings from a community-based study - Mengxing Wang; Lerong Mei; Aoming Jin; Xueli Cai; Jing Jing; Suying Wang; Xia Meng; Shan Li; Tiemin Wei; Yongjun Wang; Yuesong Pan (Cardiovascular Diabetology, 2022)
Abstract Background Insulin resistance is an important cause of cardiovascular events and cerebral infarction development. We aimed to investigate the association of the triglyceride glucose (TyG) index with atherosclerotic burden and plaques in coronary, intra- and extracranial arteries in participants with non-diabetes, and compared the results with that of the homeostasis model assessment of insulin resistance (HOMA-IR). Methods Participants without diabetes in the PolyvasculaR Evaluation for Cognitive Impairment and vaScular Events (PRECISE) study were included. We categorized participants by tertiles of the TyG index and the concordance/discordance of the TyG index and HOMA-IR. Discordance was defined as a TyG index equal to or greater than the median and HOMA-IR less than the median, or vice versa. The atherosclerosis plaques and burden in coronary, intra- and extracranial arteries were evaluated. The association of HOMA-IR and TyG index with the presence of atherosclerotic plaques and atherosclerotic burden was assessed by binary and ordinal logistic regression models, respectively. Results Among 2,719 included participants, the average age was 60.9 (± 6.6) years, and 53.0% were female. Both TyG index and HOMA-IR were associated with increased odds of coronary/intra- and extracranial atherosclerotic plaques and burden after adjustment for age, sex, currenting smoking and drinking (all P < 0.05). However, the association between HOMA-IR and intracranial atherosclerosis was not statistically significant after adjustment for all potential confounders. Discordantly high TyG index with HOMA-IR had a higher odd of extracranial plaque (odds ratio [OR]: 1.34, 95% confidence interval [CI]: 1.04–1.71), extracranial atherosclerotic burden (common odds ratio [cOR]: 1.35, 95% CI 1.06–1.71), coronary plaque (OR: 1.30, 95% CI 1.01–1.68) and segment stenosis score (cOR: 1.39, 95% CI 1.09–1.78) as compared with concordantly low TyG index with HOMA-IR. The TyG index had a better net reclassification improvement ability than HOMA-IR for atherosclerotic plaques when adding to baseline model. Conclusion Elevated TyG index was associated with increased odds of atherosclerosis in coronary/intra- and extracranial arteries. Compared with HOMA-IR, the TyG index was more strongly associated with intracranial atherosclerosis. Moreover, discordantly high TyG index with HOMA-IR was also important for atherosclerosis identification.